The Determinant Analysis of E-Commerce Tax Payer Compliance in Surakarta: PP No. 23 of 2018 - Lintang Kurniawati; Nur Kholis (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the effect of taxpayers' perceptions of PP Number 23 of 2018, taxpayer awareness, understanding of regulations, and tax rates on e-commerce taxpayer compliance in the city of Surakarta. The population of this study is e-commerce actors in the city of Surakarta. Based on certain criteria, the sample size is 100 respondents. The data collection method used a questionnaire (google form) which was measured by a Likert scale. The data analysis methods used were: (1) descriptive statistics, (2) data quality tests consisting of validity and reliability tests, (3) classical assumption tests consisting of data normality, multicollinearity, heteroscedasticity, and autocorrelation tests, (4) multiple linear regression analysis. The conclusion of this study is that there is a significant effect of taxpayer awareness and understanding of regulations on e-commerce taxpayer compliance. Meanwhile, taxpayers' perceptions of PP Number 23 of 2018 and tax rates have no effect on e-commerce taxpayer compliance.